Venkteshwar Jallaraph - Jallaraph, Venkteshwar; Pathak, K. N. (International Journal of Bio-resource and Stress Management, 2018)
This study was conducted in Bastar district of Chhattisgarh state during 2015–16 to know the awareness level of indigenous technical knowledge of paddy growers in paddy cultivation. The Ex-Post-Facto research design was used for the study. This design was considered appropriate because the phenomenon has already occurred. The sample has been selected through multi-stage sampling technique. Bastar district was selected purposively for study because of paddy is the main crop in that area. There are seven blocks (Bastanar, Darbha, Bakawand, Bastar, Jagdalpur, Tokapal and Lohandiguda) in Bastar district among which two blocks (Tokapal and Lohandiguda) were selected for study. Six villages were selected from each block. From each of the selected villages, 10 respondents were selected by simple random sampling procedure, thus the sample size for the study was 120. The primary data were collected through personal interview technique with the help of pre-tested interview schedule. Various statistical measures viz., mean, standard deviation and mean score were used for analyzing the data. In present study it was found that higher per cent of paddy growers (46.66%) had high level of awareness regarding Indigenous Technological Knowledge practices, followed by medium (39.17%) and low (14.17%), respectively. The highest extent of rank order wise awareness about field preparation and ploughing practices were Ist (2.94), followed by irrigation management practices (2.90) IInd and plant protection measure practices (2.87) IIIrd.